Study On the Path To Improve the Leadership Of Sports Counselors And Students' Employability - Wang, Xiansheng (Journal of Theory and Practice of Humanities Science, 2023)
Graduates "difficult employment" has become a prominent problem in the general college education, the so-called "graduation = unemployment" concept seriously affects the realization of the goal of talent training in colleges and universities. However, the employment channels of sports major itself are relatively narrow, and many students are engaged in jobs irrelevant to their major after graduation. Therefore, this paper aims to promote the improvement of college counselors' quality and employment rate by discussing the promotion path of sports counselors' leadership and students' employment ability. To sum up, in the face of increasingly complex computer application environment, the development of computer software has put forward more stringent and diversified requirements. Therefore, the introduction of layered technology to computer software development, constantly improve the computer software development environment, improve the development efficiency, shorten the software development cycle, save the cost of software development, so as to promote the sustainable and healthy development of computer software industry.